Peningkatan Keaktifan Belajar Dan Hasil Belajar Peserta Didik Mata Pelajaran Fikih Melalui Penerapan Model Pembelajaran Problem Based Learning (PBL) Di MI Ma’arif Ngliseng Kab. Bantul - Mohammad Hanif (Journal of Social Science and Economics, 2023)
The Problem Based Learning (PBL) model in the learning process is as follows. Stage 1 Orients students to the problem, stage 2 organizes students to learn, stage 3 guides individual and group investigations, stage 4 develops and presents the results of the work, stage 5 analyzes and evaluates the process of solving the problem. This research is Classroom Action Research (PTK) with a spiral model from Kemmis and Taggart which consists of 2 cycles. Each cycle consists of four stages including: planning, implementing, observing, and reflecting. Each cycle consists of 2 meetings. This research shows that student learning outcomes have improved after taking action. The percentage of students who have not completed has decreased from cycle 1 to cycle 2 (from 72% to 0%. The percentage of students who have completed has increased from cycle 1 to cycle 2 (from 28% to 100%). The indicator of the success of this PTK is that This PTK is said to be successful if the percentage of students whose learning outcomes have been completed reaches at least 90%. The table shows that if the percentage of students whose grades have been completed has reached 100%, then the PTK has been successful.